Optimal enoxaparin dosing strategies for venous thromboembolism prophylaxis and treatment of high body weight patients. Issue 207 (November 2021) - Martin, Annalise M.; Polistena, Paola; Mahmud, Asma; Bettridge, Brett; Morling, Alan; Chuah, Hun; Yong, Agnes S.M.; Leahy, Michael F.
Abstract: Objective: Obesity is a risk factor for developing venous thromboembolism (VTE). Optimal dosage of enoxaparin has not been established in the obese population. We aimed to study clinical outcomes and complications with enoxaparin in obese patients. Methods: A retrospective, single centre observational study of obese patients treated with enoxaparin for VTE ( n = 47) using a body mass index (BMI)-stratified dosing, thromboprophylaxis ( n = 46), and non-obese controls ( n = 20) was performed. Anti-Xa was used to measure enoxaparin efficacy. Results: Patients with a median BMI of 36.3 kg/m 2 (range 30–52.7) with a median weight of 136 kg (range 68–240) received therapeutic enoxaparin at median 120 mg BID (range 60–200). A median targeted anti-Xa level of 0.79 (95% CI 0.72–1.03) IU/mL was achieved in 58% of patients. Dose reduction, or increase was needed in 25%, and 16% patients respectively. Mild or major haemorrhage, or VTE occurred in 10%, 2% and 2% patients respectively. Patients with a median weight of 160 kg (range 130–245) received thromboprophylaxis with 40 mg BID enoxaparin. Targeted median anti-Xa of 0.22 IU/mL (95% CI 0.19–0.24) was achieved in 59% patients. Mild haemorrhage was seen in 2%, while none developed major haemorrhage or VTE. Control patients who received enoxaparin 40 mg daily did not develop VTE; 5% had minor bleeding events. Conclusions: BMI-stratified therapeutic enoxaparin dosing regimen is safe and effective therapy in obese patients. Fixed dosing without monitoring may not be appropriate. Thromboprophylaxis with 40 mg BID in obese patients was efficacious in preventing VTE without excess bleeding compared to control patients.